Nurses’ perceptions on the nursing process: an integration of qualitative studies - Maria das Graças Peregrino de Sousa Santos; Morgana Maria Ramos de Medeiros; Françoíra Queiroz de Castro Gomes; Bertha Cruz Enders (Rev Rene)
Implementation studies of the Nursing Process have registered difficulties related to the nurses’ perceptions of this methodology. The objective of this study was to synthesize the nurses’ perceptions of the Nursing Process and the problems related to its implementation in hospital practice. A meta-synthesis study was conducted in the form of integration study of qualitative research. The results of eight qualitative studies identified in the LILACS, BDENF, SCIELO data bases for the period from 2005 to 2009 were submitted to an integration and reinterpretation synthesis. Three thematic categories revealed that nurses favorably perceive the Nursing Process and its application, provided that operational changes are made so as to improve the problem of insufficient knowledge regarding its applicability as a tool for the improvement of care.